Transformasi Struktur Ekonomi Non-Migas di Provinsi Riau Tahun 2010-2022 - Nauli, Marissa; Muhammad Hidayat; Neng Murialti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
Economic development is not necessarily focused on the city center or region, but local governments can see the potential for progress and prosperity of economic development both in the regional capital and in the city center. This study aims to determine the transformation of the economic structure of Riau Province in 2010-22 by using data released by the Central Statistics Agency, namely the Gross Regional Domestic Product ADHK. By using the Location Quotient (LQ) analysis method, Shift Share Analysis, and Klassen Typology. The results of the three methods are that according to the LQ analysis, the base sector owned is the Agriculture, Forestry, and Fisheries sector; Mining and Quarrying; and Processing Industry. In terms of Shift Share, Riau Province received a surplus value with a total of 262,423.84 billion Rupiah. For the analysis of the Klassen Typology, the superior sectors are the Agriculture, Forestry, and Fisheries sectors; and manufacture.